Hubungan Kualitas Pelayanan Bermain Terhadap Perkembangan Sosial Emosional Anak di TK Negeri Pembina Kec. Kota Tengah - Tiansi Mustapa; Nuraini S. Lawadjo; Faujia Polamolo; Wanda Ayu Lestari; Sulastya Ningsih (Prodi Sastra Jepang Universitas Ngudi Waluyo, 2025)
Play activities hold an essential role in early childhood learning because they allow children to recognize different emotions, understand social rules, and develop interaction skills with those around them. This study aims to examine the relationship between the quality of play services and the social–emotional development of children aged 5–6 years at TK Negeri Pembina, Kecamatan Kota Tengah. The research employed a quantitative approach with a descriptive correlational design. A total of 14 children from Group B were selected as participants, and data were collected through direct observations during play activities as well as questionnaires completed by parents. The findings indicate that the quality of play services is categorized as good, with an average score of 23.8. Meanwhile, the children’s social–emotional development is categorized as very good, with an average score of 37.4. These results suggest that the play services provided by the school have a positive impact on children’s social and emotional growth. However, further improvements in the quality of play services are still needed to ensure more optimal stimulation. Overall, the study highlights that well-designed play services significantly contribute to supporting early childhood social–emotional development.